USING â€œBIG THINKâ€ CHANNEL ON YOUTUBE TO IMPROVE STUDENTSâ€™ WRITING SKILL AT SMA KARTIKA XX-1 MAKASSAR - Paramita, Jeshica Laura; Sahib, Nur Faizah; Fansury, Andi Hamzah (Lembaga Jurnal FKIP Universitas Bosowa, 2024)
The purpose of this research is to Improve Students Writing Skill At SMA Kartika XX-1 Makassar by using YouTube channel â€œBig Thinkâ€. This research used experimental method. This research was conducted in August 2023. This research was conducted in three steps these include pre-test, treatment, and post-test. The population in this study were students of X MIPA 1 SMA Kartika XX-1 Makassar consisting of 30 students and the writer took 30 sample students at X MIPA 1 SMA Kartika XX-1 Makassar. The results of this study that using â€œBig Thinkâ€ channel improves studentsâ€™ writing skills. It was supported by the result of mean score in pre-test and post-test. The mean score of pre-tests was 60.40 and is classified as poor. While the total mean score from the post-test is 89.63 and is classified as good. It means that implementation of the using â€œBig Thinkâ€ channel on YouTube is effective to improve writing skill at students X MIPA SMA Kartika XX-1 Makassar.